Effect of Salting on Mechanical Drying of Pangasius hypophthalmus - Kumar, Gonugodugu Praveen; K. A., Martin Xavier; Nayak, Binaya Bhusan; Kumar H, Sanath; Venkateshwarlu, Gudipati; Balange, Amjad K. (International Journal of Bio-resource and Stress Management, 2022)
A study was conducted during 2016 to evaluate the effect of salt and mechanical drying on Pangasius at Central Institute of Fisheries Education, Andheri, Mumbai, India. In this study, the salted and unsalted Pangasius was mechanically dried at 60°C temperature and the quality of the dried Pangasius was evaluated. The quality parameters include the changes in proximate composition, physicochemical parameters [total volatile base nitrogen (TVBN), peroxide value (PV), free fatty acid (FFA), pH, thiobarbituric acid reactive substances (TBARS), salt, water activity], microbial enumeration (total viable count (TVC), Escherichia coli, Staphylococcus spp.) and sensory evaluation. The colour characteristics, percentage yield and storage stability of the product was also evaluated. From the results, it was observed that the protein and ash content of unsalted dried Pangasius was higher than salt dried Pangasius. From the results of physicochemical changes, it was observed that PV, FFA, TVBN, TBARS and salt content were higher in salt dried Pangasius. The TVBN, PV and salt content of salt dried Pangasius were 24.75 mg N 100 g-1, 4.17 meq O2 kg-1 fat and 14.55% respectively which were higher than the Unsaltd dried Pangasius. The salt dried Pangasius had higher L* value but lower a* and b* value than unsalted dried Pangasius. The unsalted dried Pangasius was unstable during storage whereas salt dried Pangasius was stable. Based on the results, it was concluded that salt drying is the most effective method of preservation for drying Pangasius at 60°C.